The Root Cap Cuticle: A Cell Wall Structure for Seedling Establishment and Lateral Root Formation - Berhin, Alice; de Bellis, Damien; Franke, Rochus B.; Buono, Rafael A.; Nowack, Moritz K.; Nawrath, Christiane (Cell, 2019)
The root cap surrounding the tip of plant roots is thought to protect the delicate stem cells in the root meristem. We discovered that the first layer of root cap cells is covered by an electron-opaque cell wall modification resembling a plant cuticle. Cuticles are polyester-based protective structures considered exclusive to aerial plant organs. Mutations in cutin biosynthesis genes affect the composition and ultrastructure of this cuticular structure, confirming its cutin-like characteristics. Strikingly, targeted degradation of the root cap cuticle causes a hypersensitivity to abiotic stresses during seedling establishment. Furthermore, lateral root primordia also display a cuticle that, when defective, causes delayed outgrowth and organ deformations, suggesting that it facilitates lateral root emergence. Our results show that the previously unrecognized root cap cuticle protects the root meristem during the critical phase of seedling establishment and promotes the efficient formation of lateral roots. [Display omitted] •At early developmental stages, root caps of primary and lateral roots form a cuticle•This polyester-rich cuticle is lost with the removal of the first root cap cell layer•During germination, the root cap cuticle protects the sensitive root meristem•The cuticle of young lateral roots facilitates invasive growth and root emergence A cuticle-like cell wall structure on plant root caps protects seedlings from abiotic stress and contributes to proper lateral root outgrowth.